Social anxiety and psychological distress among polycystic ovarian syndrome patient’s in Pakistan - Ilyas, Uzma; Rafique, Saher (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the fear of negative evaluation as a predictor, and to explore the association of social anxiety with psychological correlates among women with polycystic ovaries. Method: The cross-sectional study was conducted from August 2020 to November 2021 after approval form the University of Central Punjab, Lahore, Pakistan, and comprised unmarried women aged 18-26 diagnosed with polycystic ovary syndrome. The sample was raised from different clinics and hospitals based in Lahore and Gujranwala cities. The sample was divided into obese, hirsutism and acne vulgaris groups. Data was collected using a demographic proforma along with standardised Derriford Appearance Scale, Brief Fear of Negative Evaluation Scale, University of California, Los Angeles, Loneliness Scale and the Social Interaction Anxiety Scale. Data was analysed using SPSS 24. Results: Of the 180 patients, 60(33.3%) were in each of the 3 groups. The overall mean age was 21.4+/-2.27 years. A significant association of fear of negative evaluation was found with appearance distress, social anxiety and loneliness (p<0.05). The fear of negative evaluation and appearance distress also significantly predicted loneliness in the subjects (p<0.01). The obese group scored significantly higher in terms of fear of negative evaluation and social anxiety compared to the other groups (p<0.05). Conclusion: Women with polycystic ovaries were found to be suffering from adverse psychological outcomes and social anxiety. Key Words: Social anxiety, Hirsutism, Acne vulgaris, Obesity, PCOS, Distress.